Risk factors for cardiovascular diseases in taxi drivers in Tabriz metropolis - Mohammad Saadati; Mohammad Bagher Naghizad; Mir Bahador Yazdani; Sepideh Harzand Jadidi (مجله پزشکی دانشگاه علوم پزشکی تبریز)
Background. Taxi drivers are among the high-risk groups for cardiovascular disease due to their hard working conditions, long working hours, daily stress, and low income. The present study investigated the prevalence of cardiovascular disease risk factors among taxi drivers in Tabriz metropolis. Methods. This cross-sectional study was conducted with the participation of taxi drivers in 2020. A total of 400 taxi drivers in Tabriz were included in the study using multi-stage sampling. A questionnaire was developed to collect data on demographic characteristics and the presence of cardiovascular disease risk factors in the participants or their family members. The International Physical Activity Questionnaire, the Pittsburgh Sleep Quality Questionnaire (PSQI), and the Iranian Socioeconomic Status Assessment Questionnaire were also used to collect the data. Data analysis was done using Microsoft Excel and Stata 15 software and applying the Logit model. Results. About 50% of the drivers had various degrees of overweight and obesity. In total, 30% of the drivers were suffering from high blood pressure and nearly 11.5% of them were simultaneously suffering from hypertension, hyperlipidemia, and diabetes. More than 16% of the drivers had at least a family member with hypertension or diabetes. Only 30% of drivers had good sleep quality. The three independent variables of education level below a diploma, number of working days per week, and sleep quality score of drivers had a direct relationship with a high risk of cardiovascular disease. Conclusion. The results of the study indicate the serious health challenges of taxi drivers as the main agents of intra-city transportation. Practical Implications. Regarding the taxi drivers’ hard working conditions, employing proper policies on drivers' occupational health literacy promotion, annual health monitoring, application of behavioral insights in developing interventions, and implementation of support programs addressing economic issues could be effective in reducing drivers' health risk factors.